The Mediating Role of Green Supply Chain Management and the Moderating Role Competitive Intensity in the Relationship between Environmental Orientation and Corporate Performance - Khomsan Laosillapacharoen; Preecha Karuhawanit (International Journal of Supply Chain Management, 2019)
The prime objective of the current study is to explore the nexus between the environmental orientation and the corporate performance. In addition to that the study has examined the mediating role of green supply chain management and the moderating role competitive intensity in the relationship between environmental orientation and corporate performance. The study attempted to understand the way in which the environmental orientation, green supply chain and competitive intensity affect the corporate performance. In order to narrow down the research gap identified; there is need for conducting a comprehensive analysis of the influence on GSCM created by environmental orientation. The study is among the pioneering studies on the issues. So, current study has used SEM-PLS as statistical tool to answer the research questions raised in this study and research objectives envisaged in the current study. The findings of the current study have provided support to with the hypothesized results. This study will be helpful for policymakers and researchers in examining the link between environmental orientation, green supply chain management, competitive intensity and the corporate performance. Further, it gives useful insights from managerial perspective to rectify the supply chain practices for sustaining competitive advantage.